Prediction Method and Characteristics of Static Acoustic Scattering for Marine Composite Propellers - XU, Suchen; PENG, Zilong; ZHOU, Fulin; MIU, Xuhong; KE, Huicheng (Archives of Acoustics, 2024)
This study introduces a hybrid approach to predict the acoustic scattering characteristics of composite propellers featuring variable thickness and complex curvature. The approach combines the Kirchhoff approximation (KA), which employs an intersection algorithm (IA) for determining the thickness of discrete surface elements, with the theory of orthotropic laminate transfer matrix (OLTM). The overall scattered sound field of the target is determined by solving the reflection coefficients of each surface element. To enhance computational efficiency, the scattered sound field of a complete composite propeller is ingeniously predicted by cloning mesh topology from a single propeller blade, taking advantage of the rotation symmetry characteristics of the composite propeller. The validity of this prediction method is confirmed through the finite element method (FEM) and static acoustic scattering characteristic experiments conducted on a lake. The predicted results for the target strength (TS) of the composite propeller closely align with the FEM. Additionally, the TS and time-domain echo characteristics of the steel propeller utilizing the KA exhibit strong agreement with the experimental findings. These research findings provide a significant reference value for predicting the acoustic scattering characteristics near the stern of underwater vehicles.